Digital image analysis of testicular and prostatic ultrasonographic echogencity and heterogeneity in dogs and the relation to semen quality - Moxon, Rachel; Bright, Lucy; Pritchard, Beth; Bowen, I. Mark; Souza, Mírley Barbosa de; Silva, Lúcia Daniel Machado da; England, Gary C.W. (Elsevier, 2015)
A semi-automated ultrasonographic method was developed to measure echogenicity and heterogeneity of the testes and prostate gland and relationships of these measures with semen quality were assessed in 43 fertile dogs. The relationship between animal age and body weight upon the volume of the testes, epididymal tail volume and prostate volume were also established.